Effects of Habitat Fragmentation on Genetic Diversity in Cycas Balansae (Cycadaceae) - Nguyen Minh Tam; Nguyen T. Phuong Trang; Vu T. Ha Giang; L. Triest Triest (ASEAN Journal on Science and Technology for Development, 2006)
Habitat fragmentation is a serious threat to species survival. In Vietnam, Cycas balansae has been considered as threatened species because of the reduction and fragmentation of its habitats and over-exploitation. We assessed genetic variability and the pattern of population structure among six populations sampled in four provinces: Hoa Binh, Ha Nam, Ninh Binh and Quang Ninh. Polyacrylamide gel electrophoresis was performed on leaf tissues from 152 individuals representing 6 populations of C. balansae. Six of twelve enzyme systems were used to estimate genetic diversity at population and species levels. Eleven loci were examined. The allozyme data showed high levels of genetic diversity within all populations, ranging from 0.538 in Ba Sao to 0.628 in Tan Dan (average 0.576). The maintenance of high levels of expected heterozygosity (average 0.571) and low in observed heterozygosity (average 0.347) might be related to great heterozygote deficiency and increased frequencies of rare alleles. Genetic differentiation among populations was low (Dst = 0.036 and Gst = 0.064), indicating high level of gene flow (Nm = 3.22). Isolation by geographical distance was observed, however, no significant relationship between genetic distances and geographical distances was recorded. Our studies suggest small population sizes of cycads brought about by fragmentation of its habitats, over-exploitation, and increasing number of inbred individuals within populations.